MIGRASI BURUH PADA PERKEBUNAN TEBU DI MOJOKERTO 1901-1942 - Dwi Evi Fani; Marsudi Marsudi; Ronal Ridhoi (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2022)
Afdeeling Mojokerto is the second largest contributor to sugar production in Surabaya. Land expansion competition, acceleration of production results, as well as the pressure of life and a liberal economy encourage people to turn into laborers in sugar factories and plantations. The agrarian law of 1870 had an impact on the transfer of rights of state land ownership to private entrepreneurs. This shift caused the opening of new economic sectors which created a need for wage workers. This study aims to observe the migration of sugar cane plantation workers in Mojokerto region. The result of this study shows that migration, supported by an increase in health services, a conducive environment for settlement, and improvement in transportation infrastructure, substantively also present various problems coming from changes in the spatial structure due to the massive number of native laborers who came to the area. Therefore, the novelty of the study is the position of workers at the local level in the demographic problem that arises because of migration.